The role of advanced glycation end products in fracture risk assessment in postmenopausal type 2 diabetic patients - Gao, Liu; Liu, Chang; Hu, Pan; Wang, Na; Bao, Xiaoxue; Wang, Bin; Wang, Ke; Li, Yukun; Xue, Peng (Frontiers in Endocrinology, 2022)
Objective: The objective of this study was to analyze the quantitative association between advanced glycation end products (AGEs) and adjusted FRAX by rheumatoid arthritis (FRAX-RA) in postmenopausal type 2 diabetic (T2D) patients. The optimal cutoff value of AGEs was also explored, which was aimed at demonstrating the potential value of AGEs on evaluating osteoporotic fracture risk in postmenopausal T2D patients. Methods: We conducted a cross-sectional study including 366 postmenopausal participants (180 T2D patients [DM group] and 186 non-T2D individuals [NDM group]). All the subjects in each group were divided into three subgroups according to BMD. Physical examination, dual-energy x-ray absorptiometry (DXA), and serum indicators (including serum AGEs, glycemic parameters, bone turnover markers and inflammation factors) were examined. The relationship between FRAX-RA, serum laboratory variables, and AGEs were explored. The optimal cutoff value of AGEs to predict the risk of osteoporotic fracture was also investigated. Results: Adjusting the FRAX values with rheumatoid arthritis (RA) of T2D patients reached a significantly increased MOF-RA and an increasing trend of HF-RA. AGEs level was higher in the DM group compared to the NDMs, and was positively correlated with MOF-RA (r=0.682, P<0.001) and HF-RA (r=0.677, P<0.001). The receiver operating characteristic curve analysis revealed that the area under the curve was 0.804 (p<0.001), and the optimal AGEs cut-off value was 4.156mmol/L. Subgroup analysis for T2D patients revealed an increase in TGF-β, IL-6 and SCTX in the osteoporosis group, while a decreased PINP in the osteoporosis group compared to the other two subgroups. AGEs were positively associated with FBG, HbA1c, HOMA-IR, S-CTX, IL-6 and TGF-β in T2D patients, and negatively associated with PINP. Conclusions: RA-adjusted FRAX is a relevant clinical tool in evaluating fracture risk of postmenopausal T2D patients. Our study analyzed the relationship between AGEs and FRAX-RA, and explored the threshold value of AGEs for predicting fracture risk in postmenopausal T2D patients. AGEs were also associated with serum bone turnover markers and inflammation factors, indicating that the increasing level of AGEs in postmenopausal T2D patients accelerated the expression of inflammatory factors, which led to bone metabolism disorders and a higher risk of osteoporotic fractures.